Merzaq, Abd al-Qader Muhammad. “Reading and Frames of Reference: Insights in the Book of Adonis,” Year 9, Issues 33-34 (Summer-Fall 1424 AH/ 2003 CE), Pp. 223-276. - مرزاق, عبد القادر محمد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2003)
Abd al-Qader Merzaq’s article is a study in the dialectical approach to intellectual texts in general, and literary texts in particular in the project of Adonis. He attempts to analyze its theorizing and creative problematic questions through a reading on a human civilizational level and with an open mind. Merzaq argues that this is not at all impossible, as a person may in their reading be biased towards what they hold in their convictions as true. The article addresses this subject from within the following frameworks: (1) does a reading have a frame of reference, and what is this frame of reference?; (2) objective reading and ideology; (3) reading with a frame of reference, and the share of objectivity in it; (4) language and the relationship of an indicant and that being indicated, and the problematic issues that arise; and (5) alternative readings.